IMPLEMENTASI MANAJEMEN DAKWAH TERHADAP BIMBINGAN PRANIKAH DALAM MEWUJUDKAN KELUARGA SAKINAH MAWADDAH WARAHMAH DI KUA KECAMATAN ULAWENG KABUPATEN BONE (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
The results showed that the application of da'wah management to premarital guidance in KUA, Ulaweng District, Bone Regency, namely: da'wah planning, da'wah organization, mobilization/implementation of da'wah, supervision, and evaluation of da'wah. Strengths and weaknesses in the implementation of premarital guidance to realize a sakinah, mawaddah, and warahmah family in Ulaweng District, Bone Regency, strengths (Cooperation, Human Resources, and Service), discipline at work is very important in the world of work. while the weakness is the lack of good time management because good management is an important thing that must be applied in organizations and institutions both from employees and from prospective brides who follow premarital guidance.